A proposed framework for risk assessment in highway construction - Tagaya, Victor Nazarene (Animo Repository, 2021)
The objective of the practicum is to propose a risk assessment framework for Highway Construction. In this paper, the intern discussed that the employer’s current risk assessment framework has limitations as it produces a department level assessment, causing unreliable risk importance ranking among all departments. With this, the intern proposed a framework that produces an output that perceives the assessment of employees and its implementing internal stakeholders. Risk importance index was used as the criteria for assessment and two methods were introduced to calculate the index namely Risk Appetite Method and Risk Index Method. Cronbach’s Alpha was used and included in the framework to determine the reliability of the framework. An electronic survey was made and evaluated by employees involved in highway construction and implementing internal stakeholders to assess the risks identified. Upon evaluation, 14 out of 39 risks were identified as risks that needs urgent management’s attention. With the calculated Cronbach’s Alpha of 0.8769 for occurrence rating and 0.9390 for severity rating indicates that the survey and framework was reliable. With the output of the proposed framework, the intern emphasized that the adaptation of the proposed framework will be beneficial for the employer as it produces an assessment that perceives the risk importance ranking on the company level, bridging the gap of limitations from the current framework used, as well as aiding the management to determine the allocation of resources to mitigate the occurrence of risks that needs management’s attention, and establish their risk management plans.